Learning ecologies in initial teacher education: the case of Spain - Carrasco-Aguilar, Claudia; Ortiz-Mallegas, Sebastián; Domingo Segovia, Jesús; Luzón Trujillo, Antonio (Taylor & Francis Group, 2025)
This study investigated learning ecologies in initial teacher education (ITE) in Spain, emphasising the interaction between institutions and the personal experiences of future teachers. It analysed how learning ecologies contribute to the development of secondary education teachers, focusing on both contextual and personal dimensions. The research involved a sequential qualitative approach with three phases: documentary research (six official documents and 11 interviews with course coordinators); a case study with an ethnographic approach at a public university (13 observations and 22 unstructured interviews); and three narrative interviews with prospective teachers. Findings revealed that ITE in Spain is marked by a complex interplay of educational policies, institutional practices, and personal trajectories of prospective teachers. The results highlight significant tensions between theoretical training and practical application, alongside the critical role of personal and contextual factors in shaping professional identities. Effective ITE requires a balanced integration of theoretical knowledge and practical experience, emphasising the importance of personal and contextual dimensions in learning ecologies. The findings suggest that fostering collaboration among educational institutions and aligning training programmes with the lived experiences of future teachers can enhance the quality of teacher education.
Keywords: Investigación activa en educación; Profesores - Formación profesional; Initial teacher education; Learning ecologies; Qualitative research; Teacher development; Secondary education